A randomised controlled trial of N-acetylcysteine in the management of anti-tuberculosis drug-induced liver injury - Moosa, Muhammed (Department of Medicine, 2023)
Background: Liver injury is the most common severe adverse effect of first-line anti-tuberculosis therapy (ATT). Nacetylcysteine (NAC) has efficacy in patients with paracetamol toxicity, and may be of benefit in liver injury due to other causes, such as ATT-induced liver injury (AT-DILI). Rechallenge of first line ATT after liver injury is usually attempted and may result in recurrence of liver injury. Alanine transaminase (ALT) is the biomarker currently used in AT-DILI diagnosis. MicroRNA-122 (miR-122) is a sensitive biomarker for liver injury due to paracetamol, but data on utility as a biomarker for ATDILI are limited. Methods: We conducted a randomized double-blind placebo-controlled trial of intravenous NAC in adult hospitalized participants with AT-DILI. Primary endpoint was time to ALT < 100 U/L; secondary endpoints included length of hospital stay and 8-week mortality. We described outcomes of ATT rechallenge following AT-DILI. We quantified miR-122 and ALT concentrations before and after infusion of NAC/placebo, and explored the effect of NAC on miR-122. Results We enrolled 102 participants with AT-DILI, 53 randomized to NAC and 49 to placebo. Mean age was 38 (SD±10) years, 58 (57%) were female and 89 (87%) were HIV positive. Median time to ALT